Vertical transmission explains the specific Burkholderia pattern in Sphagnum mosses at multi-geographic scale - Bragina, Anastasia; Cardinale, Massimiliano; Berg, Christian; Berg, Gabriele (Frontiers in Microbiology, 2013)
The betaproteobacterial genus Burkholderia is known for its versatile interactions with its hosts that can range from beneficial to pathogenic. A plant-beneficial-environmental (PBE) Burkholderia cluster was recently separated from the pathogen cluster, yet still little is known about burkholderial diversity, distribution, colonization, and transmission patterns on plants. In our study, we applied a combination of high-throughput molecular and microscopic methods to examine the aforementioned factors for Burkholderia communities associated with Sphagnum mosses – model plants for long-term associations – in Austrian and Russian bogs. Analysis of 16S rRNA gene amplicons libraries revealed that most of the Burkholderia are part of the PBE group, but a minor fraction was closely related to B. glathei and B. andropogonis from the pathogen cluster. Notably, Burkholderia showed highly similar composition patterns for each moss species independent of the geographic region, and Burkholderia-specific fluorescent in situ hybridization of Sphagnum gametophytes exhibited similar colonization patterns in different Sphagnum species at multi-geographic scales. To explain these patterns, we compared the compositions of the surrounding water, gametophyte-, and sporophyte-associated microbiome at genus level and discovered that Burkholderia were present in the Sphagnum sporophyte and gametophyte, but were absent in the flark water. Therefore, Burkholderia is a part of the core microbiome transmitted from the moss sporophyte to the gametophyte. This suggests a vertical transmission of Burkholderia strains, and thus underlines their importance for the plants themselves.